Returns to public agricultural and rural investments in China - Fan, Shenggen; Cho, Emily EunYoung; Rue, Christopher (Emerald Publishing Limited, 2018)
The purpose of this paper is to review China’s past returns in a period over the last 40 years to public agricultural and rural investments to highlight the importance for future strategic investments in China’s agri-food system and in rural areas.The paper synthesizes research findings from previous studies and reviews more recent trends. Based on the main findings, the authors provide forward-looking guidance for China’s investments agriculture and rural areas in the context of emerging global and domestic trends in agriculture, food security, and nutrition.Public investments in the agricultural research and development (R&D), rural education, and rural infrastructure have been shown to have significant positive returns to agricultural growth as well as to reductions in poverty and regional inequality. Returns to overall agricultural GDP were highest for agricultural R&D, followed by education, roads, and telephones. Investment in education had the greatest returns to poverty reduction, as well as to nonfarm GDP and overall rural GDP. Investment in agricultural R&D had the second greatest returns in term of poverty reduction, and was also a close second in returns to nonfarm GDP and overall rural GDP following education. The rural infrastructure spending also saw significant returns to poverty reduction, largely through growth in agricultural and nonagricultural sectors. Investments in agriculture and rural areas will continue to be important, as China and the world face emerging challenges amidst a changing global landscape, particularly regarding climate change, rapid urbanization, nutritional imbalances, and food safety concerns. In addressing these emerging challenges, continued support for agricultural R&D and innovations can play a key role.The paper highlights research findings on key investment areas that will be increasingly important for China’s agri-food system, and provides guidance in the context of emerging trends impacting food security and nutrition.